2012
DOI: 10.1289/ehp.1003270
|View full text |Cite
|
Sign up to set email alerts
|

Spatial Patterns and Socioecological Drivers of Dengue Fever Transmission in Queensland, Australia

Abstract: Background: Understanding how socioecological factors affect the transmission of dengue fever (DF) may help to develop an early warning system of DF.Objectives: We examined the impact of socioecological factors on the transmission of DF and assessed potential predictors of locally acquired and overseas-acquired cases of DF in Queensland, Australia.Methods: We obtained data from Queensland Health on the numbers of notified DF cases by local government area (LGA) in Queensland for the period 1 January 2002 throu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
103
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 92 publications
(113 citation statements)
references
References 38 publications
(43 reference statements)
10
103
0
Order By: Relevance
“…Similar results have been reported in the city of Rio de Janeiro 34 , Nova Iguaçu (Rio de Janeiro State) 35 , and Queensland, Australia 36 .…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Similar results have been reported in the city of Rio de Janeiro 34 , Nova Iguaçu (Rio de Janeiro State) 35 , and Queensland, Australia 36 .…”
Section: Discussionsupporting
confidence: 87%
“…Dengue transmission also undergoes interference from such factors as herd immunity to the various serotypes circulating in the current epidemic and in previous years 36 . Some authors found evidence of the association between dengue risk and socio-environmental conditions after the introduction of a new serotype, where after the virus spreads, the incidence rates generally occur in all socioeconomic strata 37 .…”
Section: Discussionmentioning
confidence: 99%
“…This result was different with the research conducted by Yussanti [19] that it showed a positive relationship between income per capita with the incidence of dengue, means that the higher income, the greater the possibility of being infected by dengue. It may because of people with higher economic level have higher mobility, so the chances of getting an infection from another place higher [8]. The difference results from this study and Yussanti [19] perhaps because of the different characteristics place studied.…”
Section: Socio-economic Statusmentioning
confidence: 55%
“…The difference results from this study and Yussanti [19] perhaps because of the different characteristics place studied. Research conducted by Yussanti [19] and Hu et al [8] did in urban area, while this study was conducted in sub-urban area. Inconsistencies in the results of research on the relationship between socio-economic status and the incidence of dengue may also be associated with the environmental concern.…”
Section: Socio-economic Statusmentioning
confidence: 99%
See 1 more Smart Citation